Evaluating an emergency department‐based mental health liaison nurse service: A multi‐site translational research project. (18th July 2020) - Wand, Timothy; Collett, Gemma; Cutten, Alexa; Stack, Amanda; Dinh, Michael; Bein, Kendal; Green, Timothy; Berendsen Russell, Saartje; Edwards, James; White, Kathryn
Abstract: Objective: We aimed to translate and evaluate a model of mental health liaison nursing (MHLN) care that was embedded within EDs. Methods: The 12 month mixed‐methods translational research study incorporated descriptive data on ED presentations, waiting times for MHLN intervention, time spent in ED and discharge arrangements across three EDs in New South Wales. The study involved an inner‐city ED (where the model was first established) and two rural sites. Surveys were conducted on a subset of ED patients ( n = 58), and emergency and psychiatry staff ( n = 52). Results: Triage category 3 presentations accounted for 49% of the MHLN team workload. Response times and ED length of stay varied between city and rural sites, with rural sites demonstrating prompt response times and reduced ED length of stay. The model was strongly endorsed by patients and staff, with 95% of staff and 85% of patients across the three sites recommending the model be implemented in other emergency settings. The need for adequate resources to maintain designated levels of staffing and sustain this model of care was highlighted. Conclusion: Findings from the present study indicate that a model of ED‐based MHLN care developed in a metropolitan setting was successfully translated to two rural sites. However, the model needs to adhere to certain key principles, and be adequately resourced in order to be sustainable and improve outcomes for ED patients and access to community care.